Adhyayana podu sahatika patra (samanya pela) mattamedi buddhagama visayaya asrita pasala padanam karagat agayim kriyatmaka vana akaraya pilibanda adhyayanayak - Withanage, S.U.J (My University, 2012)
This study was launched in order to meet the academic requirement of the Master of Education Degree programme of the Faculty of Education at the University of Colombo. We have witnessed a revolution in assessment programmes at schools in past ten years. Australia, Britain, Canada, Europe, New Zealand, and United States have rebuilt their assessment programmes and also many developing countries have tried to introduce formative assessment programmes to operate in parallel with summative assessments. Reconceptualization of assessment programme is required to achieve the educational goal of enabling students to be effective thinkers and problem solvers. School based Assessment programme (SBA) is one of a number of initiatives taken in 1994 by the government of Sri Lanka with a view of reform the education system to achieve above goals. The main objectives of the SBA programme were to improve students" learning process, to improve teachers" teaching process and to improve assessment process in order to make teaching and learning more efficient, effective and transform the school environment from an evaluation culture to an assessment culture. A long term allegation against the education system of Sri Lanka is the inability to assess the skills and abilities of the students through the existing examination structure in the proper manner. Therefore, a tendency of following a new direction in the process of education commenced after 1972. This new beginning is to pay attention to continues assessment system for the future development of the students. Nevertheless, various attempts made to overcome the problematic situations. Some Educators are of the view that, although the school based assessment programme that was one among the attempts made in the recent time did not create a controversy in the Education system, but also cannot be treated as a very successful feature in operation. While it was expected to study the operation of the SBA programme related to the subject of Buddhism at G.C.E. (Ordinary Level), introduced to rectify the weaknesses of the school based assessment programme in the School Education system. The identification of the methods used in the school based assessment (SBA) of the subject of Buddhism at G.C.E. (Ordinary Level). The suitability of those assessments and investigating the manner of operation of feedback programmes under SBA programme related to the subject of Buddhism. And the level of awareness of the teachers on SBA programme related to Buddhism in Ordinary level classes.